Jet heat transfer in the vicinity of a rotating grinding wheel - TORRANCE, ANDREW ARCHIBALD (Professional Engineering Publishing, 2006)
Impinging jets are known as a method of achieving high convective heat transfer coefficients. One potential application of impinging jet heat transfer is the air jet cooling of a grinding process. A grinding process generates heat that must be dissipated to avoid thermal damage. To date, this has been achieved using flood cooling with a traditional coolant such as an oil and water mixture; however, using a jet of air in its place has obvious environmental and economic benefits. For a range of grinding test configurations, results are presented of the convective heat transfer from the workpiece, along the notional plane of cut, and of the air flow velocity in a two-dimensional plane perpendicular to the workpiece. It has been shown that a boundary layer that develops around the rotating grinding wheel has the effect of displacing a peak in the distribution of the local heat transfer coefficient from the notional arc of cut. To effectively cool the grinding zone, therefore, it is necessary to penetrate this boundary layer and this can only be achieved when the jet velocity is substantially greater than the tangential velocity of the wheel.
PUBLISHED
Keywords: grinding, impinging jet, heat transfer, cooling